Chronic Pain and Prescription Opioid Use Among Socially Marginalized Nigerian Women: Exploring Supply Channels and Pathways to Misuse. (October 2022) - Nelson, Ediomo-Ubong E.; Alichie, Bridget O.
This study explores pathways to prescription opioid misuse and supply channels based on in-depth interviews with 16 socially marginalized Nigerian women suffering chronic pain. The pathways identified were medical pain treatment, prior substance use and opioid use for recreation and coping with psychological distress. Facing barriers to prescription opioids due to prescribing restrictions and provider stigma, many resorted to unlicensed chemist stores and street drug dealers for opioid analgesics, including fake and potentially harmful products. Patterns of prescription opioid misuse were woven into multiple and overlapping dynamics of marginalization shaping the lives of these women, including homelessness, sex work, substance use and intimate partner violence. Findings show a need to improve access to prescription opioids and other evidence-based approaches, framed within a trauma-informed approach to pain management. Further, integrating substance abuse treatment and pain management could make services responsive to the inter-related problems of chronic pain and prescription opioid misuse.